2021
DOI: 10.1093/mnras/stab1737
|View full text |Cite
|
Sign up to set email alerts
|

Light, medium-weight, or heavy? The nature of the first supermassive black hole seeds

Abstract: Observations of hyper-luminous quasars at z > 6 reveal the rapid growth of supermassive black holes (SMBHs $>10^9 \rm M_{\odot }$) whose origin is still difficult to explain. Their progenitors may have formed as remnants of massive, metal free stars (light seeds), via stellar collisions (medium-weight seeds) and/or massive gas clouds direct collapse (heavy seeds). In this work we investigate for the first time the relative role of these three seed populations in the formation of z > 6 SMBH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 168 publications
2
48
0
Order By: Relevance
“…However, since we are not directly interested in measuring merger rates in this work, we follow the results of Piana et al (2021b) who found that modelling delayed BH mergers had little impact on the actual growth of the SMBH. To be conservative, we also explored a model inspired by Sassano et al (2021) where BHs only merge rapidly during major mergers, assuming that the secondary BH in a minor merger is lost "wandering" in the remaining galaxy (motivated by the simulations of e.g. Bellovary et al 2019 and the observations of Reines et al 2020), and found that it makes very little difference on the overall AGN population.…”
Section: Smbh Growthmentioning
confidence: 99%
“…However, since we are not directly interested in measuring merger rates in this work, we follow the results of Piana et al (2021b) who found that modelling delayed BH mergers had little impact on the actual growth of the SMBH. To be conservative, we also explored a model inspired by Sassano et al (2021) where BHs only merge rapidly during major mergers, assuming that the secondary BH in a minor merger is lost "wandering" in the remaining galaxy (motivated by the simulations of e.g. Bellovary et al 2019 and the observations of Reines et al 2020), and found that it makes very little difference on the overall AGN population.…”
Section: Smbh Growthmentioning
confidence: 99%
“…Alternatively, heavy seeds with typical mass m • = 10 4 − 10 6 M could have formed by exotic pathways at z > 10 ( Bromm & Loeb 2003;Lodato & Natarajan 2006). While additional, alternative pathways to form massive BHs at high redshift have been described in the literature (see, e.g., Devecchi & Volonteri 2009;Davies et al 2011), including medium-weight seeds (Sassano et al 2021), the classic distinction between light and heavy seeds will be considered here for the sake of clarity. To date, it is still unknown whether light seeds, heavy seeds or, more likely, a combination of them contributed to the formation of the population of the first BHs.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative models assume a more massive origin of SMBHs in order to relax the constraints on the seeds growthrates. Indeed, heavy or intermediate-mass BHs (IMBHs), forming with 10 3 M seed /M 10 5 already at z 10 allow to more easily reach M BH ∼ 10 8−9 M by z ∼ 7 (e.g., Bromm & Loeb 2003;Omukai et al 2008;Shang et al 2010;Agarwal et al 2012;Volonteri & Bellovary 2012;Regan et al 2014;Visbal et al 2014b;Valiante et al 2016;Sassano et al 2021). On the other hand, these models generally require peculiar physical conditions whose occurrence is yet poorly constrained over cosmological contexts (e.g., Bromm & Loeb 2003;Agarwal et al 2016;Latif et al 2018).…”
mentioning
confidence: 99%
“…hν = [11.2 − 13.6] eV. stra et al 2014;Valiante et al 2016;Volonteri & Reines 2016;Lupi et al 2021b;Sassano et al 2021). The first ones can generally model directly the small-scale processes involved in the formation of BH seeds.…”
mentioning
confidence: 99%
See 1 more Smart Citation